Geopolitik Dan Isu Perbatasan Dalam Pendekatan Multidisiplin - Hanita, Margaretha (Jurnal Kajian Stratejik Ketahanan Nasional, 2018)
Recently, the national security issue has been faced with cross-border terrorism issues dominating border issues by referring to the latest cross-border terrorism event of the Marawi City occupation of the Philippines by the ISIS-affiliated Maute terrorist group. Marawi is a continuation of the issue of cross-border terrorism after similar issues in the Afghanistan-Pakistan, Pakistan-India, Uighur region to Thailand and Poso, Poso to the Southern Philippines, and a wave of cross-border terrorism from the Middle East region and countries including Indonesia and European countries to Iraq and Syria to join ISIS.Some of related studies were utilized and from those studies, showed that border issues can be approached with a defense and security management review approach, and national resilience studies. This requires understanding by linking gender, economics, anthropology, sociology, domestic law, international law and international relations studies, since it is realized that geopolitical approaches alone are not sufficient enough to examine these complex issues.